The Changing Crop Production Practices Over the Years: the Mystery of Economics - Alam, M Shahe; Quayum, M A; Islam, M A (Bangladesh Journal of Agricultural Research, 2012)
The present study was undertaken in two production environments in order to estimate the level of growth in area and production of rice and maize over the years, and to assess the level of changes in area under different crops. Applying both descriptive and inferential statistics, the study revealed that, the growth in acreage and production of maize had much accelerated rate compared to that for rice over the period 1987-88 towards 1996-97 and in the subsequent periods. In the favourable environment, the acreage under MV Boro increased by 18% in 2008-09 compared to 2004-05. In rabi season, the area under maize increased to 46% and 21% in drought prone and favourable areas, respectively. The magnitude of area changes from rice to non-rice crops under favourable area was negative. Per hectare cost of maize cultivation in drought prone area was about 13% higher than that of favourable area resulting in better net return in maize production under favourable area. Family labour, farm size and market accessibility were the important determining factors for devoting areas to maize cultivation instead of rice. DOI: http://dx.doi.org/10.3329/bjar.v36i4.11756 Bangladesh J. Agril. Res. 36(4): 657-668, December 2011